Library trends : current acquisition trends in American libraries - University of Illinois, Graduate School of Library Science (Urbana, 1952)
Print only.
Title from cover.
Each issue is concerned with one aspect of librarianship, and is planned by an invited guest editor.
Keywords: Library science -- Periodicals